2004
DOI: 10.1051/0004-6361:20034285
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen and [Fe II] in Active Galactic Nuclei

Abstract: Abstract. Near-infrared spectroscopy is used to study the kinematics and excitation mechanisms of H 2 and [Fe ] lines in a sample of mostly Seyfert 1 galaxies. The spectral coverage allows simultaneous observation of the JHK bands, thus eliminating the aperture and seeing effects that have usually plagued previous works. The H 2 lines are unresolved in all objects in which they were detected while the [Fe ] lines have widths implying gas velocities of up to 650 km s −1 . This suggests that, very likely, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
213
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(246 citation statements)
references
References 58 publications
28
213
3
2
Order By: Relevance
“…While low H 2 1−0S(1)/Brγ values appear to be characteristic of starbursts (H 2 1−0S(1)/Brγ < ∼ 0.6), classical Seyfert 1 and 2 galaxies also display a range of values (Rodríguez-Ardila et al 2004, 2005Riffel et al 2010) that are compatible with those measured in our sample. The [FeII]/Brγ ratio also shows values compatible with those observed in starbursts, although higher values would have been expected for Seyfert galaxies, such as NGC 5135 and NGC 7130 (Rodríguez-Ardila et al 2004;Riffel et al 2010;Valencia-S et al 2012). These galaxies show the highest values of the [FeII]/Brγ ratio of the whole sample, close to ∼2.0, and are similar to values reported for other Seyfert 2 galaxies (Blietz et al 1994).…”
Section: Characteristics Of the Near-ir Stacked Spectra Of Lirgs And supporting
confidence: 86%
“…While low H 2 1−0S(1)/Brγ values appear to be characteristic of starbursts (H 2 1−0S(1)/Brγ < ∼ 0.6), classical Seyfert 1 and 2 galaxies also display a range of values (Rodríguez-Ardila et al 2004, 2005Riffel et al 2010) that are compatible with those measured in our sample. The [FeII]/Brγ ratio also shows values compatible with those observed in starbursts, although higher values would have been expected for Seyfert galaxies, such as NGC 5135 and NGC 7130 (Rodríguez-Ardila et al 2004;Riffel et al 2010;Valencia-S et al 2012). These galaxies show the highest values of the [FeII]/Brγ ratio of the whole sample, close to ∼2.0, and are similar to values reported for other Seyfert 2 galaxies (Blietz et al 1994).…”
Section: Characteristics Of the Near-ir Stacked Spectra Of Lirgs And supporting
confidence: 86%
“…Larkin and coworkers reported a strong linear relation in the (log−log) [FeII]1.26 µm/Paβ−H 2 2.12 µm/Brγ plane, with starforming galaxies showing the lowest ratios, Seyferts with intermediate ratios, and LINERs with the highest ratios. Later studies of Seyfert 1 and Seyfert 2 galaxies (Rodríguez-Ardila et al 2004Riffel et al 2006) confirmed the trend first reported by Larkin and coworkers. A more recent analysis on a larger compilation of Seyfert 1 and 2 galaxies, including star-forming galaxies and a few LINERs (Riffel et al 2013a), have shown that activity in galaxies seems to follow a unique linear relation log ([FeII]1.26 µm/Paβ) = 0.749 × log(H 2 2.12 µm/Brγ) − 0.207, with star-forming galaxies showing the lowest ratios and LINERs apparently the largest.…”
Section: Introductionsupporting
confidence: 83%
“…Reunanen et al (2002) present NIR-spectroscopy of two Seyfert 1, three Seyfert 2 and one Seyfert 1.5 and show that in Seyfert 2 galaxies Fe II is generally stronger than Brγ or H 2 lines, while apparently in Seyfert 1 galaxies Brγ is stronger. Rodríguez-Ardila et al (2004) also studied H 2 and Fe II line emission in a sample of 22 (mostly) Seyfert galaxies and concluded that these lines originate in different regions due to systematically different linewidths. They detected molecular hydrogen in 90% of their sources, with the majority being excited by thermal excitation processes.…”
Section: Introductionmentioning
confidence: 99%